2022
DOI: 10.3390/molecules27248819
|View full text |Cite
|
Sign up to set email alerts
|

Phloretin, as a Potent Anticancer Compound: From Chemistry to Cellular Interactions

Abstract: Phloretin is a natural dihydrochalcone found in many fruits and vegetables, especially in apple tree leaves and the Manchurian apricots, exhibiting several therapeutic properties, such as antioxidant, antidiabetic, anti-inflammatory, and antitumor activities. In this review article, the diverse aspects of the anticancer potential of phloretin are addressed, presenting its antiproliferative, proapoptotic, antimetastatic, and antiangiogenic activities in many different preclinical cancer models. The fact that ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 91 publications
0
16
0
Order By: Relevance
“…3D), which proved that the increase in MMP after interfering LncBAG6-AS was consistent with the reduction of the membrane potential by phloretin in our previous study. 12…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3D), which proved that the increase in MMP after interfering LncBAG6-AS was consistent with the reduction of the membrane potential by phloretin in our previous study. 12…”
Section: Resultsmentioning
confidence: 99%
“…3D), which proved that the increase in MMP after interfering LncBAG6-AS was consistent with the reduction of the membrane potential by phloretin in our previous study. 12 LncBAG6-AS regulates the transcription of downstream genes instead of adsorbing miRNAs Although LncBAG6-AS was shown to be involved in the regulation of OS, the molecular mechanism of LncBAG6-AS was further explored. It is known that the subcellular localization of lncRNA significantly impacted its function.…”
Section: Interference With Lncbag6-as Expression Enhances the Activit...mentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids and their glycosides are the main active ingredients, which have diversified effects, such as anti-tumor, anti-inflammatory, anti-aging, liver protection, and antioxidant. [44][45][46][47][48] Park et al 49 measured the total phenolic content (TPC) and antioxidant activity of SBE from different solvents and found a positive correlation between TPC and oxygen radical absorbance capacity. Han et al 50 identified that the bioactive components in scutellaria baicalensis are baicalein, visidulin III, and baicalin by LC-MS combined with a bioassay, showing strong free radical 2,2 0 -azinobis-3-ethylbenzothiazoline-6-sulfonate (ABTS) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging activity.…”
Section: Introductionmentioning
confidence: 99%
“…So far, more than 40 chemical components have been identified in scutellaria baicalensis. Flavonoids and their glycosides are the main active ingredients, which have diversified effects, such as anti‐tumor, anti‐inflammatory, anti‐aging, liver protection, and antioxidant 44–48 . Park et al 49 measured the total phenolic content (TPC) and antioxidant activity of SBE from different solvents and found a positive correlation between TPC and oxygen radical absorbance capacity.…”
Section: Introductionmentioning
confidence: 99%